Are Mergers Beneficial to Consumers? Evidence from the Market for Bank Deposits - Focarelli, Dario; Panetta, Fabio (American Economic Review, 2003)
The general conclusion of the empirical literature is that in-market consolidation generates adverse price changes, harming consumers. Previous studies, however, look only at the short-run pricing impact of consolidation, ignoring effects that take longer to materialize. Using a database that includes detailed information on the deposit rates of individual banks in local markets for different categories of depositors, we investigate the long-run price effects of mergers. We find strong evidence that, although consolidation does generate adverse price changes, these are temporary. In the long run, efficiency gains dominate over the market power effect, leading to more favorable prices for consumers.